The development of self-confidence using The C3 Framework learning management with flipped classroom techniques in The S 32103 Social studies course in grade 11 students at Mattayomtaladyaiwittata School,Khon Kaen - Nummeesri, Thiwat; Tungkasamit, Angkana (Journal for Developing the Social and Community, 2023)
This research was conducted with the purpose of 1) Developing self-confidence levels in students by using a learning management method based on the C3 Framework together with Flipped Classroom techniques, and applying it to the S 32103 Social Studies class for 11th grade students at Mattayomtaladyaiwittaya School. The objective of using the method was to improve the students’ average self-confidence levels to at least a “good'' rating, where at least 70% of the students must pass the set standard. 2) Improving learning achievements by using a learning management method based on the C3 Framework together with Flipped Classroom techniques, and applying it to the S 32103 Social Studies class for 11th grade students at Mattayomtaladyaiwittaya School. The objective of using the method was to use an average of 70% as the passing standard per student, and to ensure that a minimum of 70% of students passed the set standard. The sample group used for this research were 15 11th grade students at Mattayomtaladyaiwittaya School, the Secondary Educational Service Area Office, Khon Kaen, who were studying during their 2nd term of the 2021 academic year. The research method used was the Action Research method, and the research tools used comprised 1) Tools used for testing in implementation, which were 9 lesson plans referenced from a learning management method based on the C3 Framework together with Flipped Classroom techniques, 2) Tools used to reflect the results of implementation, which were forms to record results after the learning management method was implemented, learning monitoring forms, student interview forms, self-confidence evaluation forms, a Likert rating scale of 5 levels with 20 questions, and multiple choice tests of 4 choices each at the end of each cycle, in which there were 3 cycles and 15 questions per cycle, 3) Tools used to evaluate the efficiency of the learning management method, comprising self-confidence evaluation forms based on a Likert rating scale of 5 levels, which involved 4 aspects and included 32 questions overall, learning achievement multiple choice forms of 4 choices each, in which there were 45 questions, and analyzing data with averages, percentages, and standard deviation. The results of the research found that: 1) Self-confidence levels in 11th grade students who have been subjected to the learning management method based on the C3 Framework together with Flipped Classroom techniques in the S 32103 Social Studies class, were at 4.37, which is considered a “good” rating. Moreover, 13 students overachieved passing scores, which expressed in a percentage is 86.67%, exceeding the previously set standard. Overall, students achieved higher average self-confidence scores, and over 70% passed the set standard. 2) Learning achievement scores in 11th grade students who have been subjected to the learning management method based on the C3 Framework together with Flipped Classroom techniques in the S 32103 Social Studies class were 34.80 on average, which expressed in a percentage is 77.33%, exceeding the previously set standard, which was 70% on average, and that at least 70% of students must pass the set standard.